Functional Ovarian Cysts in Artificial Frozen-Thawed Embryo Transfer Cycles With Depot Gonadotropin-Releasing Hormone Agonist - Ji, Hui; Su, Yan; Zhang, Mianqiu; Li, Xin; Li, Xiuling; Ding, Hui; Dong, Li; Cao, Shanren; Zhao, Chun; Zhang, Junqiang; Shen, Rong; Ling, Xiufeng (Frontiers in Endocrinology, 2022)
Objectives: To investigate the incidence of functional ovarian cysts, its influence on clinical rates, and proper management after depot gonadotropin-releasing hormone (GnRH) agonist pretreatment in artificial frozen-thawed embryo transfer cycles (AC-FET). Methods: This retrospective cohort study involved 3375 AC-FET cycles with follicular-phase depot GnRH agonist administration between January 2017 and December 2020. Subjects were divided into a study group (cycles with cyst formation) and a control group (cycles without cyst formation). The study group was matched by propensity scoring matching with the control group at a ratio of 1:2. For patients with ovarian cyst formation, two major managements were used: a conservative approach (i.e., expectant treatment) and a drug approach (i.e., continued agonist administration). The primary outcome was live birth rate (LBR). Results: The incidence of functional ovarian cysts following pituitary downregulation is 10.1% (341/3375). The study group exhibited a LBR similar to the control group (54.5% vs. 50.1%, adjusted odds ratio [aOR] 1.17, 95% confidence interval [CI] 0.88–1.56, P = 0.274). Patients with a lower body mass index and anti-Müllerian hormone, and a higher basal estradiol level were more susceptible to developing functional ovarian cysts. The LBR decreased after the drug approach compared with the conservative approach, but not significantly (aOR 0.63, 95% CI 0.35–1.14, P = 0.125). Following the conservative approach, cycles arrived at live births had a significantly shorter duration from the detection of functional cysts to the start of endometrium preparation (15.7 ± 5.1 days vs. 17.4 ± 5.3 days, P = 0.009) and a significantly higher proportion of ovarian cysts on the initial day of exogenous hormone supplementation (51.4% vs. 30.3%, P = 0.001). After controlling for all confounders, the differences remained statistically significant. Conclusions: It is unnecessary to cancel cycles that experience functional ovarian cyst formation. Conservative management and further agonist suppression protocol had similar pregnancy rates. However, a conservative approach was recommended due to its lower cost and fewer side effects. Our findings support a shorter waiting period when choosing the conservative protocol.